Production of Omega-3 Fatty Acid Enriched Eggs Using Pearl Millet Grain, Low Levels of Flaxseed and Natural Pigments - Amini, K.; Ruiz-Feria, C.A. (International Journal of Poultry Science, 2008)
We have previously reported that pearl millet (PM) could substitute corn and reduce the amount of flaxseed (8%, FS) needed to produce omega-3 enriched eggs in a 6 week trial, but reduced yolk pigmentation. In this experiment we evaluated egg fatty acid (FA) profile, yolk pigmentation, laying performance, and liver integrity in a 12 week experiment using PM-based diets with lower levels of FS (4, 6 and 8%) and natural pigments (PG, 0.1% and 0.2%) in a factorial arrangement of treatments (six cage replicates per treatment). Diets were formulated to be isocaloric and isonitrogenous and to meet or exceed NRC requirements. Egg number and egg mass produced were measured and recorded on a daily basis, whereas BW and feed consumption measurements were recorded every two weeks. At the end of each two week period, three eggs were collected from each cage to measure egg trait parameters and then yolks were separated, pooled and lyophilized for FA determination by Gas Chromatography. At the end of the experiment, all the hens were euthanized to determine liver integrity. Egg traits and flock performance parameters, were not different among treatments, except in week 8, 10 and 12, when birds fed PM-based diets including 8% FS produced smaller (P < 0.05) eggs than hens fed 4% FS. The inclusion of the PG at 0.1% restored yolk pigmentation to marketable levels (above 7 on the Roche® color fan scale). In summary, birds fed a diet containing PM as the sole grain source and 6% FS, consistently produced eggs with more than 350 mg/egg of n-3 FA, which is the lower standard to market eggs as “omega-3 enriched”, whereas hens fed the diet containing 8% FS produced eggs with about 500 mg/kg of n-3 FA. Liver integrity was not affected by dietary treatment. Thus, PM based diets with levels as low as 6% of FS and low levels of natural PG (0.1%) can be used to produce n-3 FA enriched eggs, preserving egg quality and restoring yolk color, and maintaining hen health and productive performance.